Factors associated with football injuries in Malawi: implications for physiotherapy intervention - Mughogho, Anderson (University of the Western Cape, 2015)
Background: Physiotherapists are part of the medical team involved in prevention and management of football injuries in Malawi. However, in Malawi no physiotherapist is currently involved in prevention and management of football injuries in the Malawi Super League. Aim: The aim of the study was to determine the need for physiotherapy intervention in prevention and management of football injuries. Methodology: A concurrent mixed method study design was used to collect data. A self administered questionnaire was used to collect quantitative data from football players. Qualitative data was collected through in-depth interviews from team doctors and coaches respectively. Quantitative data was analysed using the SPSS version 20.0. Descriptive data was presented in the form of percentages, means, ranges, standard deviations, and frequencies using tables, figures and graphs. A chi-square test of association and Fischer’s exact test were used to study the factors associated with football injuries against prevalence of injury. Audiotaped interviews were transcribed verbatim and expressed ideas were read several times, coded and reduced into categories and themes. Ethical clearance was granted by the University of the Western Cape and relevant authorities in Malawi. Results: A response rate of 67.5% was obtained. The mean age of football players was 21.73 (SD=3.295) years. The injury prevalence was 68.9% with 64% of injuries occurring during matches and 37% during training. The majority (84%) of the injuries were sustained in the lower limbs and 52.7% of the players who reported to have incurred an injury had recurring injuries with the ankle joint (33.3%) being the most affected part. Ligament sprain was the most common type of injury (36%) and most of the injuries (36.5%) reported were severe. No medical professional is available to manage injuries during training while team doctors are always available during matches. Recurrent injury was significantly associated injury prevalence (P=0.000). Use of protective gear was also significantly associated with injury prevalence both at training (P<0.01) and matches(P<0.05). Both coaches and team doctors reported that recurrent injury, psychological, player fitness, and lack of equipment were factors contributing to injury prevalence. Regarding injury management, coaches and team doctors reported sprains and strains as the most common injuries seen in the league. Furthermore, their views regarding injury prevention were sought. Team doctors perceived use of protective equipment as the main strategy of injury prevention while coaches regarded warm up as the main injury preventative strategy. Conclusion: There is need for physiotherapy intervention in prevention and management of football injuries in Malawi. === Magister Scientiae (Physiotherapy) - MSc(Physio)